Synthesis and structural consideration of metal-organic framework (MOF) coordination polymer with various metal linker ratios - Misran, H.; Aminuddin, A.M.; Zini, F.A.M.; Singh, R. (Engineering, 2011)
Metal-organic framework MOF-5 (i.e. IRMOF-1) with the chemical structure of Zn(4)O(BDC)(3) were successfully synthesized using room temperature synthesis approach of direct-mixing method ans liquid-crystal templating method. The metal clusters organic linker used was benzenedicarboxylic acid (BDC). Direct-mixing approach resulted in MOF-5 with tetragonal cell while the liquid-crystal templating method resulted in cubic structure. The metal/linker ratios were varied from 0.1 to 1 to study the effect of metal linker on the formation of MOF-5 materials and their characteristics. The crystallinity of the evacuated framework MOF-5 materials were increased when the metal/organic linker ratios were increased from 0.3 to 0.5. However, the cubic structure of the evacuated framework was relatively disrupted at metal/linker ratio 0.7.